Bilateral Deficit During Jumping Tasks: Relationship With Speed and Change of Direction Speed Performance. Issue 7 (July 2021) - Bishop, Chris; Berney, Jake; Lake, Jason; Loturco, Irineu; Blagrove, Richard; Turner, Anthony; Read, Paul
Abstract : Abstract: Bishop, C, Berney, J, Lake, J, Loturco, I, Blagrove, R, Turner, A, and Read, P. Bilateral deficit during jumping tasks: relationship with speed and change of direction speed performance. J Strength Cond Res 35(7): 1833–1840, 2021—Research to date has investigated the phenomenon of the bilateral deficit (BLD); however, limited research exists on its association with measures of athletic performance. The purpose of this study was to investigate the magnitude of the BLD and examine its relationship with linear speed and change of direction speed (CODS) performance. Eighteen physically active and healthy university students performed double- and single-leg countermovement jumps (CMJs), drop jumps (DJs), and standing broad jumps (SBJs) to calculate the BLD across jump tasks. Subjects also performed 10- and 30-m sprints and a 505 CODS test, which were correlated with all BLD metrics. Results showed varying levels of BLD across CMJ metrics (jump height, peak force, eccentric impulse, concentric impulse, and peak power), DJ metrics (ground contact time and flight time), and the SBJ (distance). However, a bilateral facilitation was shown for jump height and reactive strength index during the DJ test. The main findings of this study were that: (a) a larger BLD in CMJ height related to a faster 505 COD (left leg) ( r = −0.48; p = 0.04), 505 COD (right leg) ( r = −0.53; p = 0.02), and COD deficit (right leg) ( r = −0.59; p = 0.01), (b) a larger BLD in CMJ concentric impulse related to faster 505 COD (left leg) ( r = −0.51; p = 0.03), 505 COD (right leg) ( r = −0.64, p = 0.01), and COD deficit (right leg) ( r = −0.60; p = 0.01), and (c) a larger BLD in DJ flight time related to a faster 505 COD (left leg) ( r = −0.48; p = 0.04). These results suggest that a larger BLD is associated with faster CODS performance, but not linear speed. This highlights the individual nature of the BLD and may support the notion of developing movement competency on one limb for enhanced CODS performance.